Bioenzyme-responsive l-arginine-based carbon dots: the replenishment of nitric oxide for nonpharmaceutical therapy. (5th October 2021) - Han, Chuyi; Yu, Qinghua; Jiang, Junhao; Zhang, Xianming; Wang, Fan; Jiang, Mingyue; Yu, Ruihong; Deng, Tao; Yu, Chao
Abstract : The design and synthesis of a series of novel l -arginine-based carbon dot NO-donating drugs for vasodilation and tumor suppression. Abstract : Nitric oxide (NO) is a short-lived, bioactive gas that has been found to have affinitive effects on cardiovascular diseases as well as cancer biology, while NO deficiency may cause serious pathological responses. The existing chemically-synthesized NO donors have inevitable systemic toxicity and cannot be released adaptively. Hence, l -arginine, an endogenous NO precursor, merits investigation as a natural efficient NO donor. Herein, we designed amino acid-doped l -arginine CDs-based bioenzyme-responsive NO donors, which could adaptively replenish NO/ONOO − in response to different microenvironments. Our results indicated the mechanism of the NO/ONOO − supplementation of l -arginine-based CDs and their potential for nonpharmaceutical gas-involving theranostics for the first time.